2010
DOI: 10.1016/j.jnutbio.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, yeast expression, purification and biological activity of a truncated form of the soybean 7S globulin α′ subunit involved in Hep G2 cell cholesterol homeostasis

Abstract: A truncated form of alpha' chain (talpha'), the soybean 7S globulin subunit previously demonstrated to be active in controlling the cholesterol and triglyceride homeostasis in in vitro and in vivo models, was cloned and expressed in the yeast Pichia pastoris. The recombinant polypeptide spanned 216 amino acid residues from the N-terminal side and included the N-terminal extension region of the soybean subunit. The talpha' polypeptide was purified by conventional biochemical techniques, and its potential to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Some investigations have shown that its α′ subunit may have a major role in the cholesterol-lowering properties of soybean (Consonni et al, 2010(Consonni et al, , 2011Duranti et al, 2004). Other authors have focused attention on the isolation and characterization of hypocholesterolaemic peptides from soy protein hydrolyzates.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have shown that its α′ subunit may have a major role in the cholesterol-lowering properties of soybean (Consonni et al, 2010(Consonni et al, , 2011Duranti et al, 2004). Other authors have focused attention on the isolation and characterization of hypocholesterolaemic peptides from soy protein hydrolyzates.…”
Section: Introductionmentioning
confidence: 99%
“…However, many microorganisms can easily be genetically engineered to produce well-characterized feed proteins from non-microbial sourcesor even produce entirely novel, customized proteins with superior digestibility, tailor-made amino acid profiles and reduced allergenic potential. A number of genes encoding seed storage proteins from plants have successfully been inserted into the genomes of yeast for recombinant protein production at laboratory scale (Consonni et al 2010;Lin et al 2004;Medina-Godoy et al 2006). Such recombinant (and potentially customized) feed protein could allow for a higher inclusion threshold than endogenous microbial protein, potentially to a degree where it could completely replace conventional sources of protein feed.…”
Section: Possible Routes Towards Producing Edible Microbial Biomass Fmentioning
confidence: 99%
“…Recently, two studies demonstrated the ability of a truncated form of the vicilin α subunit (tα ) (Consonni et al, 2010) and a recombinant polypeptide α E polypeptide (α E) (Consonni et al, 2011), in modulating cholesterol homeostasis and the activity of the LDL receptor in HepG2 cells. By monitoring the uptake and degradation of 125 I-LDL, it was demonstrated that the treatments with tα or α E produced significant increases in LDL uptake and degradation, similar to those found in cells incubated with simvastatin (a potent inhibitor of cholesterol biosynthesis).…”
Section: Downloaded By [West Virginia University] At 06:37 20 Novembementioning
confidence: 99%